ANA - A framework for building ATHENA on ARM. (September 2015) - Smith, Joshua Wyatt; Hamilton, Andrew
Abstract: The ATLAS software framework (ATHENA) is large and dynamic, comprised of around 6.5 million lines of code. It is compiled using the ATLAS monitoring system, NICOS which uses tools and scripts located and tuned for the CERN services, LXPLUS and AFS. Furthermore, the constraints placed on the hardware that the software is based, limits compilations to traditional x86 architecture. With the sudden interest in ARM processors for large scale high energy physics computing, a new system needs to be implemented to build ATHENA versions for ARM, on ARM. This letter serves to introduce a building framework called Atlas Nightly on ARM (ANA). This new framework implements patches to suit the ARM architecture with the goal of a final ATHENA version for ARM.